The Building up of Students’ Vocabulary Mastery through Knowing by Heart Strategy - Ahmed Sardi (Sekolah Tinggi Agama Islam Negeri Majene, 2022)
The purpose of this research was positively to find out whether the knowing by heart strategy is applicable/ effective or not to build up the student’s vocabulary mastery of SMPN 2 Patampanua especially for the second year. In sum, this research was adopted by experimental research design. The population of this research was the second year students of SMP Negeri 2 Patampanua Pinrang in 2012-2013 academic years, which are spread out in 246 students. Then, the sample was taken from VIII.6 with amount 40 students and VIII.4 on amount 40 students. The sample selected by using cluster random sampling technique toward total sample 80 students. The data was obtained by distributing instrument as multiple choice tests and filling the blank test. The overall result of data analysis showed that the mean score on post-test of experiment class (73,06) was higher than the post-test of control class (66,69), and the t-test value (3,593) was greater than t-table value in the level (2,021). However, alternative hypothesis failed to be rejected. It could be concluded that the application of the knowing by heart strategy as the first applied strategy was able to build up the student’s vocabulary mastery in learning English at SMPN 2 Patampanua for the second year.